HUBUNGAN PENDAMPING PERSALINAN DENGAN KECEMASAN IBU BERSALIN DI KLINIK KASIH IBU KECAMATAN GALANG KABUPATEN DELI SERDANG - Sri Wulan; Kuat Sitepu; Rahmad Gurusinga; Herlina Barus (JURNAL ILMIAH DHDT - KEBIDANAN, 2020)
Unattended labor will have the effect of fear that can cause tension and cause his disorder, and eventually labor runs smoothly. Childbirth companions plays an important role in the birth process. Loving support reduces the mother's need for pain medication and medical intervention in labor. The purpose of this study was to determine the relationship of labor companions and maternal anxiety. This research was conducted at the Kasih Ibu Clinic, Galang Subdistrict, Deli Serdang Regency in November - December 2019. The type of research in this study was an analytic survey. The population of this research is all mothers who will give birth at the Ibu Kasih Clinic, Galang District, Deli Serdang Regency. The sampling technique used was accidental sampling with a total sample of 30 people. The test used in this study is the Chi-quare test. The results showed that there was a relationship between labor companion and maternal anxiety where p nilai 0.05 (p = 0.024). The presence of childbirth companions especially the husband is expected in the delivery room and the husband is expected to continue to carry out his role in providing physical and emotional support to the mother especially during the labor process.